Pola Komunikasi Ulul Azmi dalam Menghadapi Para Penentang - Baharuddin, Baharuddin; Abdullah, Abdullah; Sikumbang, Ahmad Tamrin (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This paper examines Ulul Azmi's communication patterns in dealing with opponents. The Prophets who are classified as Ulul Azmi are the five great prophets mentioned in the Qur'an, namely Prophets Nuh, Ibrahim, Musa, Isa, and Muhammad (PBUH). They are known for their steadfastness, patience and steadfastness in facing various obstacles, including rejection and resistance from their people. The communication patterns of the Ulul Azmi prophets in dealing with opponents consisted of rational, patient, firm, symbolic, prayer and threat approaches. They not only use words, but also actions and deeds that convey deep moral and theological messages. Even though they are often faced with rejection and strong resistance, the Ulul Azmi prophets remain steadfast in carrying out their duties to convey revelations and invite people to believe in Allah.